The Allegory of the Cave and Plato’s Epistemology of Politics - Świercz, Piotr (Folia Philosophica, 2019)
The aim of this article is to analyze Plato’s epistemology of politics in the light of Book VII of the Republic, in which the Allegory of the Cave is introduced. The problem named in the title is presented within the framework of a veritative interpretation of Greek ontology (referencing Charles Kahn’s work) and against the backdrop of Plato’s polemic with sophistry (Protagoras and Gorgias), along with references to the sources of Plato’s inspiration – the Eleatics and Pythagoreans. In my analysis I propose hypotheses concerning certain aspects of the Cave Allegory (e.g. the status of the fire) and present my interpretation of Plato’s politico-philosophical project.